The Roles of Alliances in Governments’ Relationships Between Bangladesh and Indonesia Epoch of H. E. Sheikh Hasina and H. E. Joko Widodo: The Case of Rohingya Refugees (2017–2020) - Mohammad Eisa Ruhullah; Dyah Mutiarin; Suswanta (Research and Development Agency Ministry of Home Affairs, 2021)
Indonesia is one of the first nations to formally acknowledging Bangladesh's independence that is in February 1972. However, there is lacking scientific study on both government relations. To solve the Rohingya crisis in Bangladesh from Myanmar. This study analyzes the roles of alliances in government relationships between Bangladesh and Indonesia in the epoch of prime minister Shaikh Hasina and President Joko Widodo, the Rohingya refugee (2017-2020). This qualitative research operates secondary data; Qualitative Descriptive (QD) is a form used in the qualitative study for comprehensive thoughts, expressly regulating the relevant phenomena. The research questions, what kind of challenges Indonesia and Bangladesh friendship faced on the Rohingya issue? How did both nations overcome, and what are the roles in their governmental alliances played? The study found that both countries have effective diplomatic administrative regulations. Indonesian government's efforts in the case of Rohingya are very active compared to other Asian countries. In reply to the Rohingya emigrant crisis and the maintaining of reciprocal settlement with the Bangladesh government in focusing of Indonesia diplomacy, is to find the arrangement of the refugee dilemma by approaching the root elements of the puzzle and intensifying the collaboration in determining the crisis. In short, the Bangladesh government appreciated the efforts of the Indonesian authority by mutual relationships even the friendship is upon the reciprocal agreement. It suggests that both governments should maintain an equal or more friendly bilateral settlement to keep these diplomatic relations effective and fruitful for both nations.